Pengaruh Kompensasi terhadap Kinerja Karyawan pada PT. Tunggal Abadi di Serang, Banten - Jeffry Adriansyah; Puji Laksono; Cecep Warman (Jurnal Tadbir Peradaban, 2021)
This study aims to determine the effect of compensation on employee performance at PT. Tunggal Abadi in Serang, Banten. The method used is explanatory research with a sample of 98 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this research variable compensation obtained an average score of 3,415 with good criteria. Employee performance variable obtained an average score of 3.849 with good criteria. Compensation has a positive and significant effect on employee performance with the value of the regression equation Y = 10.347 + 0.824X, and the correlation coefficient value of 0.765 or has a strong relationship with a determination value of 58.5%. Hypothesis testing obtained a significance of 0.000 <0.05.